POTENSI PENGEMBANGAN KOMODITAS COKLAT (THEOBROMA CACAO L.) DI KABUPATEN HALMAHERA BARAT - Rahmat Mamuasi; Datje Renjaan; Faisal Y Habsyi (Jurnal Pendidikan dan Ekonomi (JUPEK), 2026)
Cocoa (Theobroma cacao L.) in West Halmahera Regency has high agro-climatic potential, but its productivity is still hampered by traditional cultivation technology, limited capital, and weak post-harvest management. This research formulates a sustainable development strategy focusing on plant rejuvenation, strengthening cooperative institutions, and improving post-harvest processing skills. Through an integrated approach in potential sub-districts such as Jailolo and Sahu, this strategy is expected to increase product added value, create jobs, and improve the welfare of local farmers. Cocoa productivity in West Halmahera Regency is hampered by traditional technology and post-harvest processing, despite its highly favorable agro-climatic potential. This research formulates a locally-based development strategy, including rejuvenation, access to capital, and downstream processing, to increase farmer incomes and establish the region as a center for quality cocoa. Visit the local government's official website for more information on the cocoa development program.